Desarrollo de una preparación farmacéutica sólida: tabletas con actividad normoglicemiante a partir de las hojas de moringa oleífera (moringa) - Valverde Duran, Sergio Andres (2015)
In Ecuador Diabetes mellitus according to the last census INEC in 2013, is the leading cause of death in Ecuador, having about 4695 deaths per year, here is the need to investigate the possible production of new phyto, and bailing knowledge ethnopharmacological to help control this disease, which is why the overall objective of this research is the development of a tablet formulation from the leaves of moringa (Moringa oleifera) with normoglicemiante activity. This research was conducted at the Academic Unit of Chemical Sciences and Health at the Technical University of Machala, collecting leaves of Moringa oleifera (moringa) from the Academic Unit of Agricultural Sciences, the quality control of the drug was conducted , as is residual moisture and ash with results within normal considered, likewise hydroalcoholic extracts at 15, 30 and 50% were obtained and the respective quality control covering refractive index, density, in Ecuador Diabetes mellitus was according to the latest census INEC in 2013, is the leading cause of death in Ecuador, having about 4695 deaths per year, here is the need to investigate the possible production of new phyto, and bailing ethnopharmacological knowledge to help control this pathology, which is why the overall objective of this research is the development of a tablet formulation from the leaves of moringa (Moringa oleifera) with normoglicemiante activity.